2017
DOI: 10.1186/s40608-017-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary macronutrient composition on lipid metabolism-associated factor gene expression in the adipose tissue of chickens are influenced by fasting and refeeding

Abstract: BackgroundBroiler chickens are compulsive feeders that become obese as juveniles and are thus a unique model for metabolic disorders in humans. However, little is known about the relationship between dietary composition, fasting and refeeding and adipose tissue physiology in chicks. Our objective was to determine how dietary macronutrient composition and fasting and refeeding affect chick adipose physiology during the early post-hatch period.MethodsChicks were fed one of three isocaloric diets after hatch: hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Similar results have been reported in 10- (Honda et al 2017) and 13-day-old chicks (Saneyasu et al 2013b). However, Wang et al (2017) reported that 3 h of fasting significantly reduced mRNA levels of ATGL in clavicular fat in 4-day-old broiler chicks fed a high-carbohydrate diet. One possible explanation is that the decrease in mRNA levels of ATGL may result from the suppression of adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results have been reported in 10- (Honda et al 2017) and 13-day-old chicks (Saneyasu et al 2013b). However, Wang et al (2017) reported that 3 h of fasting significantly reduced mRNA levels of ATGL in clavicular fat in 4-day-old broiler chicks fed a high-carbohydrate diet. One possible explanation is that the decrease in mRNA levels of ATGL may result from the suppression of adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…Plasma triglycerides concentrations increased linearly with increasing levels of BSFL intake, whereas a higher plasma NEFA concentration in L30 compared to L10 and the CON groups was observed. High plasma NEFA concentrations in the L30 group can be explained by either a high lipolysis rate due to a low dietary energy intake or a high intake of dietary fat (Wang et al, 2017a). Birds of the L30 group showed a lower ME intake which might be associated to higher plasma NEFA levels.…”
Section: Blood Metabolites Concentrationsmentioning
confidence: 89%
“…The results showed that the mRNA level of AGPAT9 was higher in the subcutaneous adipose tissue of fed chickens compared to fasted or refed chicks (P < 0.05). It was also greater in fed than refed chicks (P < 0.05) in abdominal adipose tissue [ 64 ]. In this experiment, the expression of AGPAT9 was significantly lower in the slow-growing group, which suggests that the fast-growing chickens might have a high fat content.…”
Section: Discussionmentioning
confidence: 99%